THE INFLUENCE OF INSTAGRAM SOCIAL MEDIA MARKETING ON FROZEN SEAFOOD PRODUCT BRAND AWARENESS : A Case Study at ICS FOOD Sidoarjo (Agridevina : Berkala Ilmiah Agribisnis, 2022)
ICS Group is an Indonesian seafood industry founded in 1987. One of the problems faced by the company is growing brand awareness in consumers' minds through Instagram. According to Instagram followers’ ICS Food accounts, the study aims to find out the use of Instagram's social media marketing influences the brand awareness of frozen seafood. The research method used is quantitative, while the data analysis used is multiple linear regression. The sample in this study is 65 respondents, and the techniques used are non-probability sampling techniques with the approach of purposive sampling. The results of this study indicate that the social media marketing carried out by ICS Food is classified as good but has not entirely made consumers aware of the existence of the ICS Food brand as one of the frozen seafood brands in Indonesia. It concluded that the social media marketing of ICS Food's Instagram account had a positive effect on brand awareness of ICS Food's frozen seafood products. Researchers recommend ICS Food to increase interaction activities with followers through interactive activities on Instagram social media accounts, such as opening question and answer sessions and taking advantage of other Instagram features. DOI : https://doi.org/10.33005/adv.v11i1.3091